Influence of cooking methods on antinutritional factors, oligosaccharides and protein quality of underutilized legume Macrotyloma uniflorum. (May 2021) - Vashishth, Rahul; Semwal, A.D.; Naika, Mahadeva; Sharma, G.K.; Kumar, Rahul
Graphical abstract: Highlights: Extrusion processing significant influenced phenolic profile of horse gram varieties. Extrusion processing caused significant reduction in antinutritional content of horse gram. Microwave processing had significant positive impact on protein quality (BV and PER). All processing methods had significant impact on oligosaccharide content. Abstract: Macrotyloma uniflorum is a salubrious but underutilized legume mainly consumed in semi-arid zones of Africa, Australia and India. Various antinutritional factors- phytates, oxalates and oligosaccharides- has limited its consumption. Current work describes the influence of various thermal processing technologies – autoclaving, microwave, micronization and extrusion- on antinutritional profile, phenolic acid profile and protein digestibility of two selected varieties. Significant (p ≤ 0.05) reduction in antinutritional content was observed for horse gram grains processed using various thermal technologies. Among all processing technologies extrusion caused marked degradation in antinutritional components. The reduction in oxalic acid, trypsin inhibitor, phytates and tannins ranged from 33 to 87 %, 77–82%, 33–60% and 51–66% respectively. Further, the decline in content of various oligosaccharides viz. raffinose, stachyose and verbascose varied from 36 to 61 %, 25–49% and 30–74% respectively for both the varieties. Although extrusion caused significant (p ≤ 0.05) decrease in the essential amino acid index and protein efficiency ratio, simultaneous increased was observed in biological value. The processing had significant (p ≤ 0.05) impact on grain antinutritional content and also retained its substantial functional properties. This establishes the utility of grain and promote the introduction of these new grains and enlarge the market of novel healthy foods.